The Use of Invasive and Non-Invasive Electrodes in Novel Technology of Upper Limb Prostheses: A Current Review - Terrazas-Rodas, Dana (2023)
n amputation is the mutilation of a body part, which can be a limb or part of a limb. For the World Health Organization (WHO), amputees represent approximately 0.25% and 1.25% of the world's population. Electrodes are used to capture biological signals or biosignals from specific parts of a user's body for optimal development of devices such as upper limb prostheses. In this review, various electrodes used in upper limb prostheses were identified in categories that are indispensable for their development, such as commercial name or electrode references, the type of electrode (invasive or noninvasive), the number of electrodes used, the control biosignals that are captured by the electrodes and that activate the operation of the prostheses, the location of the electrodes, the advantages and disadvantages, and the level of amputation of the limb. According to the research, the two advantages most mentioned by the authors are that the electrodes are cheap and accurate, while the disadvantages are that they are noisy and imprecise. These depend on the application or objective that the author wanted the electrode to have for the design of bionic hand for people who have suffered an upper limb amputation.